2022
DOI: 10.3389/fpsyg.2022.825322
|View full text |Cite
|
Sign up to set email alerts
|

Acute Aerobic Exercise-Induced Motor Priming Improves Piano Performance and Alters Motor Cortex Activation

Abstract: Acute aerobic exercise has been shown to improve fine motor skills and alter activation of the motor cortex (M1). The intensity of exercise may influence M1 activation, and further impact whole-body motor skill performance. The aims of the current study were to compare a whole-body motor skill via a piano task following moderate-intensity training (MIT) and high-intensity interval training (HIIT), and to determine if M1 activation is linked to any such changes in performance. Nine subjects (seven females and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…13,43,[45][46][47][48][49][50][51][52][53][54][55] One goal of this pilot study was to design an OLT program that was aerobically stressful while incorporating other training concepts that could only be implemented overground. Based on the assumption that each individual would arrive at their own unique movement solution to the biomechanical and bioenergetic demands of the task 14,15,67 (ie, overground walking), we proposed an aerobically challenging protocol to take advantage of multiple mechanisms of motor learning, 40,[68][69][70][71][72][73][74][75] and perhaps most importantly, while doing so in an ecologically valid environment (ie, overground). 15,67,76,77 Our findings of improved walking endurance and phase II Vo 2 onkinetics serve as preliminary evidence that our approach to OLT offers a viable option to enhance walking distance while concurrently addressing cardiorespiratory impairments in this population.…”
Section: Discussionmentioning
confidence: 99%
“…13,43,[45][46][47][48][49][50][51][52][53][54][55] One goal of this pilot study was to design an OLT program that was aerobically stressful while incorporating other training concepts that could only be implemented overground. Based on the assumption that each individual would arrive at their own unique movement solution to the biomechanical and bioenergetic demands of the task 14,15,67 (ie, overground walking), we proposed an aerobically challenging protocol to take advantage of multiple mechanisms of motor learning, 40,[68][69][70][71][72][73][74][75] and perhaps most importantly, while doing so in an ecologically valid environment (ie, overground). 15,67,76,77 Our findings of improved walking endurance and phase II Vo 2 onkinetics serve as preliminary evidence that our approach to OLT offers a viable option to enhance walking distance while concurrently addressing cardiorespiratory impairments in this population.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 30 min of treadmill running resulted in improved motor skill acquisition of a SVIPT conducted immediately afterward, but not in subsequent retention; this improvement was driven by changes in accuracy, rather than speed ( Statton et al, 2015 ). Furthermore, Moriarty et al (2022) found improved motor learning via a piano task following moderate-intensity exercise but not high-intensity exercise. Whether an acute bout of exercise affects motor skill acquisition, retention, or both in HD, is unknown.…”
Section: Introductionmentioning
confidence: 97%